2010
DOI: 10.1186/1471-2164-11-640
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of the skin in the 'hairpoor' (HrHp) mice by microarray analysis

Abstract: BackgroundThe transcriptional cofactor, Hairless (HR), acts as one of the key regulators of hair follicle cycling; the loss of function mutations is the cause of the expression of the hairless phenotype in humans and mice. Recently, we reported a new Hr mutant mouse called 'Hairpoor' (HrHp). These mutants harbor a gain of the function mutation, T403A, in the Hr gene. This confers the overexpression of HR and HrHp is an animal model of Marie Unna hereditary hypotrichosis in humans. In the present study, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Hp homozygote mice and identified genes that were differentially expressed compared with wild-type skin (13). Among these genes, we found that Foxe1, a Forkhead family member, was significantly downregulated in Hr Hp …”
Section: /Hrmentioning
confidence: 94%
See 4 more Smart Citations
“…Hp homozygote mice and identified genes that were differentially expressed compared with wild-type skin (13). Among these genes, we found that Foxe1, a Forkhead family member, was significantly downregulated in Hr Hp …”
Section: /Hrmentioning
confidence: 94%
“…Hp mice (0.64-fold expression level compared with that of wild-type mice at P0) (13). In addition, Msx1 was recently classified as a Foxe1 target in the developing epithelial cells of the palatal shelves (20).…”
Section: /Hrmentioning
confidence: 99%
See 3 more Smart Citations